2020
DOI: 10.1002/lary.28441
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signaling molecules as treatment targets in head and neck squamous cell carcinoma

Abstract: Objectives: To evaluate BCL-2 family signaling molecules in head and neck squamous cell carcinoma (HNSCC) and examine the ability of therapeutic agents with variable mechanisms of action to induce apoptosis in HNSCC cells. Methods: messenger ribonculeic acid (mRNA) expression of BAK, BAX, B-cell lymphoma (Bcl-2), BCL2 Like 1 (BCL2L1), and MCL1 were measured in The Cancer Genome Atlas (TCGA) head and neck cancer dataset, as well as in a dataset from a cohort at Montefiore Medical Center (MMC). Protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…We next investigated why could AS and/or SRP inhibit CTXinduced myelosuppression. It is well-known that the increased expression of pro-apoptotic factor Bax and the decreased expression of anti-apoptotic factor Bcl-2 can activate the cleavage of casepase3 and induce apoptosis (20). In the present study, CTX induced BHMSC apoptosis by down-regulation of Bcl-2 and upregulation of Bax, with activation of caspase3.…”
Section: Discussionsupporting
confidence: 55%
“…We next investigated why could AS and/or SRP inhibit CTXinduced myelosuppression. It is well-known that the increased expression of pro-apoptotic factor Bax and the decreased expression of anti-apoptotic factor Bcl-2 can activate the cleavage of casepase3 and induce apoptosis (20). In the present study, CTX induced BHMSC apoptosis by down-regulation of Bcl-2 and upregulation of Bax, with activation of caspase3.…”
Section: Discussionsupporting
confidence: 55%
“…We observed markedly increased expression of activated caspase-3 in the CTEN-knockdown cancer cell cultures compared to control siRNA-treated paired samples (median positive staining % nuclei per high power field: 5.19 (siCtrl, IQR 4.94–6.16) vs. 0.85 (siCTEN, IQR 8.46–10.14), p = 0.0027, respectively) with Western blot confirmation. Ow et al [ 41 ] found, in two independent datasets, that BCL2L1 and MCL1 are the most significantly elevated anti-apoptotic markers in HNSCC. We therefore analysed the TCGA HNSCC database for correlation between CTEN and pro-apoptotic CASP3 and anti-apoptotic BCL2L1 and MCL1 [ 42 , 43 ] ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…For head and neck tumors, bortezomib does not significantly inhibit proliferation-related pathways, such as STAT3, and has no significant effect on the expression of EGFR; therefore, it has poor efficacy in HNSCC in drug experiments and clinical applications [ 27 , 28 ]. Nevertheless, the role of PIs in the treatment of other tumors still provides new thinking for the treatment of head and neck tumors, and some studies are currently underway [ 29 31 ]. This study, for the first time, elucidated the effect of proteasome inhibition on the UPP and PSMB8 in laryngeal and hypopharyngeal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%